Assessment Of Supply Chain Management Perfomance On Distribution And Transportation Management Process – Case Study At Baja Mas Malang - Calvin Hansel (Journal of International Conference Proceedings (JICP), 2018)
This research analyzes the Supply Chain Performance Management Appraisal on transportation distribution and management process at Baja Mas. The objectives of this research were (1) Assess the supply chain structure ofproducts of building tools in UD Baja Mas (2) Conduct performance measurement of supply chain management (SCM) for product of building tools in UD Baja Mas. (3) how effective the performance of supply chain management in the distribution and transportation management processes. how to collect data that is with the use of several methods that is with literatu study to compare existing theory and previous research and survey and questionnaire Keywords : Supply Chain Management, distribution process, transportation management, effective, perfomance